KAJIAN RISIKO PADA PEMBANGKIT LISTRIK TENAGA SURYA DI NUSA PENIDA - Redaksi Tim Jurnal (Sekolah Tinggi Teknik PLN, 2015)
Inadequacy of a Solar Power Plant (SPP) due to inaccuracy analysis of feseability studies conducted, based on the results of the wisnuresearch (2012) that SSP Nusa Penida are still major obstacles in technical problems and maintenance.This research aims to devise a benchmark for risk management guidelines, especially solar power plants in Nusa Penida. Djohandiputro (2004) argues that there are five cycles of risk management, ie risk identification, risk measurement, risk mapping, models of management, supervision and risk control.To design a risk management assessment guidelines, research was conducted using qualitative research methodology by using a variant of case study research. Data was collected through secondary data from studies and research reports (Wisnu, 2012) then the primary data in the form of interviews, followed by a risk assessment, risk management PLN working papers, as well as data analysis techniques.In risk management, PT PLN (Persero) published a technical manual preparation of risk assessments, is the same as it has been argued by Djohandiputro (2004) by the published memos no: 00024/030 / KDIVMRO / 2014 concerning the technical manual and paper work risk assessment dated June 16th, 2014 and regulations of the Board of Directors PLN no: 03355.K / DIR / 2014 on Risk Management in the Environment PLN dated July 22nd 2014 as the reference for researchers to make a reference to the risk management guidelines for PLTS Nusa Penida.